An Analysis of Pronunciation Error Frequency in Selected English Words among EFL Learners - Qurinta Shinta; Hetty Catur Ellyawati (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Pronunciation errors remain a persistent challenge for learners of English as a Foreign Language (EFL) in this case students of Tourism Department, particularly in words with complex syllable structures, consonant clusters, and morphological endings. This study investigates the frequency and types of pronunciation errors, including phonetic deviations, produced by 22 EFL learners when pronouncing the words messages, colleagues, lunches, and stretch. Using a quantitative descriptive design, participants’ spoken productions were recorded, transcribed using the International Phonetic Alphabet (IPA), and analyzed. Findings indicate that errors were most frequent in words with consonant clusters and plural morphemes, reflecting first-language phonological transfer and orthographic interference. Pedagogical implications for targeted pronunciation instruction and technology-assisted learning are discussed.